2022
DOI: 10.3390/ijms23031673
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal Light Pollution Induces Weight Gain in Mice and Reshapes the Structure, Functions, and Interactions of Their Colonic Microbiota

Abstract: In mammals, the daily variation in the ecology of the intestinal microbiota is tightly coupled to the circadian rhythm of the host. On the other hand, a close correlation between increased body weight and light pollution at night has been reported in humans and animal models. However, the mechanisms underlying such weight gain in response to light contamination at night remain elusive. In the present study, we tested the hypothesis that dim light pollution at night alters the colonic microbiota of mice, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…When restricting the control groups to patients with obesity, there were still significant reductions in alpha diversity among patients with NAFLD compared with controls. This phenomenon indicates that although obesity may affect the diversity of the gut microbiome (Sarmiento et al, 2022), NALFD could play a more crucial role in decreasing the gut microbial diversity. The integration of LEFSE-based and Random Forest methods identifies crucial genera that significantly decreased in the occurrence or development of NAFLD.…”
Section: Discussionmentioning
confidence: 98%
“…When restricting the control groups to patients with obesity, there were still significant reductions in alpha diversity among patients with NAFLD compared with controls. This phenomenon indicates that although obesity may affect the diversity of the gut microbiome (Sarmiento et al, 2022), NALFD could play a more crucial role in decreasing the gut microbial diversity. The integration of LEFSE-based and Random Forest methods identifies crucial genera that significantly decreased in the occurrence or development of NAFLD.…”
Section: Discussionmentioning
confidence: 98%
“…Since we aimed to isolate the impact of pollutant gases on the cultivable communities, we standardized the effect of gases with non-gas-exposed communities, similar to what has been applied in other microbial community studies [ 24 , 25 ]. This approach ensured an unbiased and more specific analysis of our data, considering the observed variation in meteorological factors among sites, like temperature ( Figure 1 D), a known driver of the environmental microbial structure [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, to isolate the impact of the pollutant gases between sites on the cultivable communities and exclude the influence of other environmental differential factors between sites, the abundances of ASVs in each gas-exposed community (g+) were standardized based on their counterparts’ non-gas-exposed community (g−) for all microbial analyses. For this, samples with zero (0) relative abundance in the g− condition were replaced with a one (1) since any number divided by one is equal to the number itself; therefore, the abundance difference between g+ and g− was maintained [ 24 , 25 ]. Hence, the input data were the nine abundance g+/g− ratios obtained for each ASV (three g+ replicates and three g− replicates) of each condition.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, paradoxical light exposure, such as dim light at night can alter the composition, relative abundance, and daily oscillations of the gut microbiota 170 . Interestingly, mice exposed to dim light at night had a significant difference in microbial diversity compared to mice exposed to standard light/dark photoperiod 171 . Furthermore, studies have shown that photoperiod disruption results in the down-regulation of genes that promote beneficial host immune responses, while genes related to the synthesis and transport of endotoxin LPS are up-regulated 17 .…”
Section: Interplays Between Circadian Rhythms and Gut Microbiotamentioning
confidence: 96%